Pengaruh Tingkat Pendidikan dan Implementasi Total Quality Management Terhadap Kinerja Pegawai Pada Badan Pengelolaan Keuangan Kabupaten Pidie Jaya - Rahmi Rahmi; Nelly Nelly; Noraizza Noraizza (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study aims to determine the magnitude of the effect of Education Level and Implementation of Total Quality Management on Employee Performance at the Financial Management Agency of Pidie Jaya Regency either simultaneously or partially. The population in this study were all employees of the Financial Management Agency of Pidie Jaya Regency as many as 64 people where all employees were sampled using the census sampling technique. The data analysis method used in this research is multiple linear regression analysis. The results showed that the level of education and the implementation of total quality management simultaneously and partially had a positive and significant effect on employee performance at the Financial Management Agency of Pidie Jaya Regency. The value of the correlation coefficient shows that the degree of relationship (correlation) between the independent variable and the dependent variable with the value of education level (X1) is 31.4% and the implementation of total quality management (X2) is 25.1%, meaning that the performance of employees at the Regency Financial Management Agency Pidie Jaya has a close relationship with the level of education and implementation of total quality management. While the coefficient of determination (R) of 81.7% means that the education level factor (X1) and the implementation of total quality management (X2) have a strong relationship to the performance of employees at the Financial Management Agency of Pidie Jaya Regency